Extracellular protease production regulated by nitrogen and carbon sources in Trichoderma reesei. (4th January 2021) - Sun, Yu; Qian, Yuanchao; Zhang, Jiaxin; Wang, Yifan; Li, Xihai; Zhang, Weican; Wang, Lushan; Liu, Hong; Zhong, Yaohua
Abstract: The filamentous fungus Trichoderma reesei is an important producer of industrial enzymes, and possesses abundant extracellular protease genes based on the genome sequence data. However, the production of extracellular proteases remains poorly understood. Here, protease production was extensively investigated on different carbon (glucose and lactose) and nitrogen sources ((NH4 )2 SO4, NaNO3, peptone, and corn steep liquor). It was found that protease production was dominantly regulated by nitrogen sources. Organic nitrogen sources were beneficial for protease production, while the preferred nitrogen source (NH4 )2 SO4 inhibited the expression of proteases. As for carbon sources, lactose was a more effective inducer than glucose for protease production. The protease activity was further examined by protease inhibitors, which suggested that protease activity was predominantly inhibited by phenylmethanesulfonyl fluoride (PMSF) and slightly suppressed by ethylenediaminetetraacetic acid (EDTA). Moreover, proteomic analysis revealed a total of 29 extracellular proteases, including 13 serine proteases, 6 aspartic proteases, and 10 metalloproteases. In addition, seven proteases were found to be present among all conditions. These results showed the regulatory profile of extracellular protease production in Trichoderma reesei grown on various carbon and nitrogen sources, which will facilitate the development of T. reesei to be an effective workhorse for enzyme or high‐value protein production in industry.